Investigation of E-Health Acceptance Factor - Ni Wayan Purnawati; Djoko Budiyanto Setyohadi; Suyoto Suyoto (JURNAL INFOTEL, 2018)
The E-Health is used to support information technology to maximize the tasks and medical services in the hospital. However, the hospital’s management still have some issues due to E-Health implementation, particularly in the interaction with the system. This study identifies significant factors affecting the implementation of E-Health. Testing a model has been done, to identify factors affecting E-Health acceptance. Quantitative Research methods has been done is implemented in this research, by conducting a survey of 150 respondents on health practitioners in the District Hospital of Gunung Mas Province of Central Kalimantan. Random Sampling Method has been done is performed by doctors, nurses, medical record officers, and midwives. Meanwhile, model testing has been done with Structural Equation Model (SEM) analysis technique. The results of this study show that computer self-efficacy factor is the most powerful factor influencing user's opinion about perceived ease of use and perceived the usefulness of E-Health (significant p <0.05), followed by compatibility, top management support, information quality, system quality, facilitating condition, service quality, complexity, and adaptability. Hospital management needs to work together as a team effort to medical practitioners to apply E-Health in hospitals. Supports and awareness from various parties, such as government, IT support, and resources are expected to help implement E-Health in rural areas. The result of this study could be a decision in taking steps to implement E-Health in the future, in order to improve services of people in rural areas.